A manual of laboratory and diagnostic tests - Fischbach, Frances Talaska; Dunning, Marshall Barnett (Philadelphia : New Delhi ; Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)
"Now in its Eighth Edition, this leading comprehensive manual helps health professionals deliver safe, effective, and informed care for patients undergoing diagnostic tests and procedures. The book covers a broad range of laboratory and diagnostic tests and studies that are delivered to varied patient populations in varied settings. Tests are grouped according to specimen and function/test type. Each test is described in detail, with step-by-step guidance on correct procedure, tips for accurate interpretation, and instructions for patient preparation and aftercare."--BOOK JACKET.
1. Diagnostic testing -- 2. Blood studies : hematology and coagulation -- 3. Urine studies -- 4. Stool studies -- 5. Cerebrospinal fluid studies -- 6. Chemistry studies -- 7. Microbiologic studies -- 8. Immunodiagnostic studies -- 9. Nuclear medicine studies -- 10. X-ray studies -- 11. Cytologic, histologic, and genetic studies -- 12. Endoscopic studies -- 13. Ultrasound studies -- 14. Pulmonary function, arterial blood gases (ABGs), and electrolyte studies -- 15. Prenatal diagnosis and tests of fetal well-being -- 16. Special diagnostic, special specimen collection, and postmortem studies -- App. A. Standard precautions for prevention and control of infection -- App. B. Guidelines for specimen transport and storage -- App. C. Vitamins in human nutrition -- App. D. Minerals in human nutrition -- App. E. Effects of drugs on laboratory tests (blood, "whole" plasma, serum, stool, and urine) -- App. F. Examples of forms.
Includes bibliographical references and index.
Keywords: Diagnosis, Laboratory -- Handbooks, manuals, etc; Clinical Laboratory Techniques -- Laboratory Manuals; Diagnostic Techniques and Procedures -- Laboratory Manuals